Analytical evaluation of polymeric CNTs/CuO nanocomposite electrode for the room temperature detection of volatile organic compounds (VOCs) - Amir Ali Khan; Ali Bahadar; Muhammad Hussain; Fida Ullah; Amir Ullah; Sufian Rasheed (Results in Chemistry, 2023)
In this study, we report the synthesis of a polymeric composite electrode based on carbon nanotubes (CNTs) and copper oxide nanoparticles (CuO NPs) for the detection of volatile organic compounds (VOCs). The CNTs were functionalized and opened using the reflux method, followed by filling with CuO NPs to prepare the CNTs/CuO nanocomposite. The prepared CuO NPs-functionalized CNTs were dispersed in polyvinylidene difluoride (PVDF) to fabricate the polymeric composite electrode. X-ray powder diffraction (PXRD) and transmission electron microscopy (TEM) were used to investigate the crystallographic and morphological characteristics of the prepared CNTs/CuO nanocomposite, which revealed spherical CuO NPs embedded in the carbon nanotubes. Cyclic voltammetry was used to evaluate the electrolytic activity of the prepared polymeric CNTs/CuO nanocomposite. In addition, the performance of the prepared polymeric CNTs/CuO nanocomposite was evaluated using a multimeter setup for the detection of various volatile organic compounds (VOCs) such as acetone, ethanol, and formaldehyde. The voltage generated at the surface of the polymeric CNTs/CuO nanocomposite electrode decreased over time due to the reduction of the VOC concentration at the surface of the electrode. Overall, this study highlights the potential of polymeric composite electrodes for the detection of VOCs and their cost-effectiveness, energy efficiency, and eco-friendliness.